Use of antimicrobial mouthwashes (gargling) and nasal sprays by healthcare workers to protect them when treating patients with suspected or confirmed COVID‐19 infection - Burton, MJ; Clarkson, JE; Goulao, B; Glenny, AM; McBain, AJ; Schilder, AGM; Webster, KE; Worthington, HV (Wiley, 2020)
Background COVID‐19 infection poses a serious risk to patients and – due to its contagious nature – to those healthcare workers (HCWs) treating them. If the mouth and nose of HCWs are irrigated with antimicrobial solutions, this may help reduce the risk of active infection being passed from infected patients to HCWs through droplet transmission or direct contact. However, the use of such antimicrobial solutions may be associated with harms related to the toxicity of the solutions themselves, or alterations in the natural microbial flora of the mouth or nose. Understanding these possible side effects is particularly important when the HCWs are otherwise fit and well.